Ecological Management Concepts as Predictors of Entrepreneurial Orientation among Senior Secondary School Students in Kogi State, Nigeria - Mathew , Bolaji Aledare; Onimisi , Agnes Ozohu; Ejide , Oluremi Felicia (Kashere Journal of Education, 2025)
This study investigated how ecological management knowledge influences the entrepreneurial orientation of senior secondary school students in Kogi State, Nigeria. The study was driven by the need for education to promote environmentally responsible innovation and sustainable business development among youths. A mixed-method design was adopted, involving 712 SS II Biology students and 14 Biology teachers selected using multi-stage sampling techniques. Data were collected through a structured questionnaire and a semi-structured interview guide. Descriptive statistics, Kruskal–Wallis, and Ordered Logistic Regression were used for quantitative analysis, while thematic analysis was used for interview responses. Results showed that students held positive perceptions of ecological management as a contributor to entrepreneurial development (weighted mean = 3.57). The Kruskal–Wallis test revealed significant differences in entrepreneurial orientation based on ecological knowledge (χ² = 22.89, p = 0.027), while the regression model identified ecological knowledge as a significant predictor of entrepreneurial orientation (β = 3.28, p = 0.019). Qualitative findings also indicated that ecological topics such as aquaculture and biodiversity conservation stimulate creativity and practical business interest. The study concludes that ecological management knowledge enhances entrepreneurial orientation and recommends curriculum strengthening, teacher training, and school-based eco-enterprise initiatives